Reading to learn on screens: challenges for research - Pereira, Iris Susana Pires (2016)
Reading on screen is the subject matter at issue, focusing on online reading to build knowledge and learn. I begin by defining core features of digital reading, taking the essential characteristics of reading on paper as a reference point. I identify and discuss some of the potentialities and requirements established by digital reading at the meaning-making process level. Eventually, I examine the most relevant research questions that emerge from the discussion for DigiLitEY.